Saponin determination, expression analysis and functional characterization of saponin biosynthetic genes in Chenopodium quinoa leaves. (September 2016) - Fiallos-Jurado, Jennifer; Pollier, Jacob; Moses, Tessa; Arendt, Philipp; Barriga-Medina, Noelia; Morillo, Eduardo; Arahana, Venancio; de Lourdes Torres, Maria; Goossens, Alain; Leon-Reyes, Antonio
Highlights: We quantified saponin content in quinoa leaves treated with methyl jasmonate. We found that methyl jasmonate induces accumulation of saponins in quinoa leaves and induces the expression of saponin biosynthetic genes in quinoa. Reference genes for qPCR analysis were identified by bioinformatics analysis of available RNA-Seq data. We cloned three genes involved in saponin biosynthesis. We characterized these genes by functional analyses in yeast. Abstract: Quinoa ( Chenopodium quinoa Willd.) is a highly nutritious pseudocereal with an outstanding protein, vitamin, mineral and nutraceutical content. The leaves, flowers and seed coat of quinoa contain triterpenoid saponins, which impart bitterness to the grain and make them unpalatable without postharvest removal of the saponins. In this study, we quantified saponin content in quinoa leaves from Ecuadorian sweet and bitter genotypes and assessed the expression of saponin biosynthetic genes in leaf samples elicited with methyl jasmonate. We found saponin accumulation in leaves after MeJA treatment in both ecotypes tested. As no reference genes were available to perform qPCR in quinoa, we mined publicly available RNA-Seq data for orthologs of 22 genes known to be stably expressed in Arabidopsis thaliana using geNorm, NormFinder and BestKeeper algorithms. The quinoa ortholog of At2g28390 ( Monensin Sensitivity 1, MON1 ) was stably expressed and chosen as a suitable reference gene for qPCR analysis. Candidate saponin biosynthesis genes were screened in the quinoa RNA-Seq data and subsequent functional characterization in yeast led to the identification of CqbAS1, CqCYP716A78 and CqCYP716A79 . These genes were found to be induced by MeJA, suggesting this phytohormone might also modulate saponin biosynthesis in quinoa leaves. Knowledge of the saponin biosynthesis and its regulation in quinoa may aid the further development of sweet cultivars that do not require postharvest processing.